2011
DOI: 10.1021/ml200263y
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of Regulators of G Protein Signaling (RGS) Proteins

Abstract: Recently regulators of G protein signalling (RGS) proteins have emerged as potential therapeutic targets since they provide an alternative method of modulating the activity of GPCRs, the target of so many drugs. Inhibitors of RGS proteins must block a protein-protein interaction (RGS-Gα), but also be cell and, depending on the therapeutic target, blood brain barrier permeable. A lead compound (1a) was identified as an inhibitor of RGS4 in a screening assay and this has now been optimised for activity, selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 26 publications
(50 reference statements)
2
78
1
Order By: Relevance
“…RGS proteins are considered difficult drug targets due to their canonical function of inhibiting signaling through a direct and transient protein-protein interaction with the a subunit of heterotrimeric G proteins (Tesmer et al, 1997). Despite this, significant progress has been made in developing RGS protein inhibitors (Roman et al, 2007;Blazer et al, 2010Blazer et al, , 2011Blazer et al, , 2015Turner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RGS proteins are considered difficult drug targets due to their canonical function of inhibiting signaling through a direct and transient protein-protein interaction with the a subunit of heterotrimeric G proteins (Tesmer et al, 1997). Despite this, significant progress has been made in developing RGS protein inhibitors (Roman et al, 2007;Blazer et al, 2010Blazer et al, , 2011Blazer et al, , 2015Turner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of RGS proteins might alter GPCR signaling in a pathway-and tissue-specific manner (Blazer and Neubig, 2009). Although RGS proteins are considered to be difficult drug targets (Tesmer et al, 1997), we and others have made significant progress in developing RGS protein inhibitors (Roman et al, 2007;Blazer et al, 2010Blazer et al, , 2011Turner et al, 2012). In other cases, however, increasing RGS protein function may be therapeutically beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we (Zhong and Neubig, 2001; and others (Doggrell, 2004;Riddle et al, 2005;da Costa Goncalves et al, 2008) suggested that RGS proteins, including RGS2, might represent novel cardiovascular therapeutic targets. Although significant progress has been made in identifying RGS inhibitors (Blazer et al, 2011;Turner et al, 2012), enhancing RGS action is more challenging .…”
mentioning
confidence: 99%
“…This idea has been bolstered by the intriguing phenotypes observed in mice carrying RGS-insensitive Ga mutants, which showed that blocking RGS actions potentiates neurotransmitter actions and linked behaviors in a targeted fashion (Talbot et al, 2010;Lamberts et al, 2013). While initial efforts focused on the identification and development of peptide inhibitors of RGS proteins as proof of concept (Jin et al, 2004;Wang et al, 2008), more recent work has focused on the development of small molecule inhibitors with the goal of treating multiple diseases, including neurologic disorders (Blazer et al, , 2011Roman and Traynor, 2011;Turner et al, 2012;Storaska et al, 2013). Thus far, RGS4 has been the main focus for the development of small molecule RGS inhibitors.…”
Section: Discussionmentioning
confidence: 99%